PERAN GURU AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN AGAMA ISLAM DI SMP AL-ISLAM 1 SURAKARTA TAHUN AJARAN 2023/2024 - Abdullah, Uwais Faqihuddin; Sukari, S; Sugiyat, S (MAMBA'UL 'ULUM, 2025)
This research took place at an educational institution under the auspices of the Al-Islam Surakarta foundation. This research aims to determine the role of Islamic teachers in increasing students' interest in learning in Islamic religious subjects at SMP Al-Islam 1 Surakarta as well as the obstacles and solutions experienced by teachers. In this research, a qualitative descriptive method was used, namely analyzing events and understanding existing phenomena, then creating a comprehensive and complex picture. The results of this research indicate the role of Islamic religious teachers in increasing students' interest in learning, inhibiting factors and supporting factors for Islamic religious teachers in increasing students' interest in learning at SMP Al-Islam 1 Surakarta. The research results show that there are several factors that become obstacles in increasing students' interest in learning, namely: 1) less varied learning methods, 2) lack of motivational support from parents. The supporting factors are: 1) motivation from the students' parents, 2) adequate infrastructure at school, 3) facilities that support learning at home